The Influencing Factors Related To The Development Of Revenue: Retribution On The Testing And Calibration Quality Of Goods And The Effect Of The Service Performance Of Women On Customer Satisfaction - Heriberta, Heriberta; Hastuti, Dwi; Aprilistiani, Lely; Zamzami, Zamzami (Opción, 2019)
A good English ability is needed in the global society that is a part of the current globalisation era. With the opening of the global market, the job com- petition is greater than before and Indonesia must have reliable and compet- itive human resources prepared by universities, including the universities in Manado. This study aims to explore the relationship between student gender and their choice of learning strategies as well as the frequency of their use. The subject of this research is the university students in Manado and the main instrument used is the Strategy Inventory of Language Learning. The findings show the differences in the choices made regarding learning strategies and their frequency of use. Among the six categories of language learning strate- gies, gender differences tend to be seen in the use of compensation strategies and social strategies in favour of male university students.